Obtaining New Liquid Fire Extinguishing Compositions and Investigation of Their Physical and Chemical Properties - Sabirov, Erkaboy Erkinbayevich; ugli Sadirov, Azizbek Tairbek; Kurbanbaev, Shukhrat Ergashevich (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents experimental experiments on the production of new liquid fire extinguishing compositions and the study of their physical and chemical properties. It is known that for high efficiency of fire extinguishing it is important to accurately deliver fire extinguishing agents over long distances to the place of ignition. Therefore, indicators such as stability, ductility and viscosity are important in determining the fire extinguishing effectiveness of liquid fire extinguishing compositions. Studies have shown that the viscosity of slurry containing 2% bentonite and 98% water is much higher than other slurries.